Model for the Development of Science and Humanities Curriculum in Islamic Universities - Alparslan Acikgence (TSAQAFAH, 2012)
This paper  elaborates  the model  for  the  curriculum  development of science and humanities for Islamic university. The model is based on the theory of  worldview, the process of which begins from learning life structure, world structure and extends to the concept of knowledge, human and value. The last three concepts are sought at university  level, yet the curriculum at this level should be directed, at the first place towards scientific mentality. Therefore, students should acquire skills and know-how as well as critical  thinking to  reach such mentality , rather  than to  give huge load of courses unnecessarily . With  those principles action plan  for the curriculum development of our universities should be as follows: Two or three courses at  introductory  level; Two  or  three  required courses  in  sub-fields  of   the  students; Two  or  three  elective course in the field of  the student; Two courses in Islamic scientific tradition; One or two courses in the methodology and logic of  Islamic scientific tradition; Two courses in the philosophy and adab of Islamic scientific tradition; The rest are elective courses such as logic, and introductory courses in philosophy and sociology . To be conversant of Islamic scientific tradition, for example student should be given a good grounding in the history of Islamic scientific tradition. The course to be given for this purpose is not a  simple history of  science  in  Islamic  civilization;  it  is  rather a course which  is designed to teach the historical continuity of Islamic scientific tradition.